IMPLEMENTASI PROGRAM SISTEM INFORMASI DESA (SID) DI KECAMATAN SINGINGI KABUPATEN KUANTAN SINGINGI - Anisah, Siti; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Forest The Village Information System Program (SID) is a village empowerment program set out in the regulations of the Regent Kuantan Singingi Regency. This program is a set of tools and processes for utilizing data and information to support resource management at the village level. The purpose of this study was to find out how the Implementation of the Village Information System Program (SID) in Singingi District, Kuantan Singingi Regency and the factors that inhibited it. The theory used is the theory of Donald Van Meter and Carl. E. Van Horn, there are six indicators that affect implementation: Policy standards and objectives; Resource; Inter-organizational communication and strengthening activities; Characteristics of implementing agents; Social, economic and political conditions; and the disposition of the implementor. This study uses a type of qualitative research with a phenomenology approach and the data needed both primary and secondary is obtained through interviewing, observation and documentation techniques for further analysis using dataanalysis techniques interactive. The results of this study indicate that: first, the Implementation of the Village Information System Program (SID) in Singingi District, Kuantan Singingi Regency is not optimal. Second, the factors that hinder the program of the Village Information System Implementation Program (SID) in Singingi District, Kuantan Singingi Regency, namely: human resources, policy resources, inter-organizational communication and activity strengthening, assessment of target groups (public opinion), economic conditions, political conditions and implementor cognition/ understanding of the implementor.                                                                                                                          Keywords: Village Information System, Public Policy, Implementation, Program